EFFECTIVENESS OF COGNITIVE LEARNING THEORY ASSISTED BY MATH TTS MEDIA TO INCREASE LEARNING MOTIVATION OF GRADE IV STUDENTS AT SDN 1 BANGSRING : EFEKTIVITAS TEORI BELAJAR KOGNITIF BERBANTUAN MEDIA TTS MATEMATIKA UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA KELAS IV DI SDN 1 BANGSRING - Suci Alvinnia Dewi; Siti Napisah; Fajar Wahyu Prasetyo (BIMBINGAN DAN KONSELING BANYUWANGI, 2025)
Learning motivation is an individual's drive or desire to do something to achieve a goal or ideal. Often students feel that studying is a boring activity, especially in mathematics subjects, quite a few students feel that mathematics is difficult and scary. So researchers provide a solution for treating cognitive learning theory assisted by mathematics TTS media as a tool for researchers to increase students' learning motivation. The method used in this research is primary data from questionnaire results and research design using a quasi-experimental design using an experimental group and a control group. The sample in this study used fourth grade students at SD Negeri 1 Bangsring. The normality test uses Kolmogorov-Smirnov with the significance value α = 0.05 and the results for the experimental group are 0.200 and the control group is 0.200, which means both groups have a normal distribution. In the data analysis of the hypothesis results with the provision of a sig value. < 0.05. Known sig value. (0.003) < 0.05 and tcount 3.419 > ttable 2.093, it can be concluded that there is effectiveness of cognitive learning theory assisted by mathematics TTS to increase the learning motivation of class IV students at SDN 1 Bangsring, which means the Ha hypothesis is accepted. accepted